PROBLEM BEZROBOCIA W OBLICZU MASOWEJ EMIGRACJI ZAROBKOWEJ - Ślebarska, Katarzyna (Śląskie Studia Historyczno-Teologiczne, 2023)
The article undertakes two critical topics that occurs currently in our country, namely unemployment and occupational emigration. Unemployment is a great sociological and psychological problem that has existed in Poland since 1990, and has become one of the crucial issues that needs effective solution. However during last two years the number of people without work has been rapidly decreasing, from about 17 per cent in 2006 to 11 per cent in 2008, the main reason of this variation refers to great occupational emigration, rather than to economical resolution. Moreover, the vision of potential return of temporary occupational emigrants leaves this problem still opened.